Comparison of ELISA using recombinant LipL32 and sonicated antigen of leptospira for detecting bovine leptospirosis - Martinez, Mara Leila (2021)
Leptospirosis is one of the most widely distributed zoonosis in the world. Bovine leptospirosis is a serious problem in bovine production, causing reproductive losses. The aim of this work was to compare recombinant LipL32 with sonicated antigen for detecting anti-Leptospira IgG antibodies in bovine serum using ELISA. The Microscopic Agglutination Test (MAT) is used as the gold standard. Sonicated antigen from cultures of Leptospira interrogans serogroup Icterohaemorrhagiae serovar copenhageni (strain M20) was used for the eELISA and rLipL32 for the rELISA. The performance of these assays was evaluated using serum samples from 166 bovines, 69 MAT positive and 97 MAT negative. At the optimal cut-off point recommended by the receiver operating characteristic (ROC) curve analysis, the sensitivity and specificity values were 98.6% and 97.9%, respectively, for eELISA, and 85.5% and 86.6% respectively, for rELISA. The value for the area under the ROC curve was 0.998 (0.994-1.0) (CI 95%) for eELISA and 0.929 (0.891-0.968) (CI 95%) for rELISA. The ROC curves for rLipL32 and sonicated antigen showed statistically significant differences (z = -3.826; p = 0.000). A three-way comparison showed statistically significant differences in the sensitivity and specificity of rELISA and eELISA. Our results showed that eELISA was more specific and sensitive than rELISA. The difference in performance (eELISA-rELISA) was 13.4% (4.03-23.28) (CI 95%) for sensitivity and 11.34 % (4.07-19.56) (CI 95%) for specificity. Our results show that the eELISA has a better diagnostic performance than rELISA for the detection of anti-Leptospira IgG antibodies in bovine serum.